“She’s a Family Member”: How Community Health Workers Impact Perinatal Mothers’ Stress Through Social-Emotional Support and Connections to Programs and Resources - Justin Rex; Nichole Fifer; Karen D. Johnson-Webb; Maddi Menich; Alyissa Horn; Carly Salamone; Holly T. Renzhofer Pappada; Camelia Arsene; Crystal Martin; Malcolm Cunningham (Health Equity)
Introduction: This study examines whether being a client in the Northwest Ohio Pathways HUB program reduces stress and improves mental wellbeing for perinatal mothers. The HUB works to improve health by connecting mothers to community health workers (CHWs) who assess mothers’ risk factors and connect them to evidence-based care pathways to reduce known risks associated with adverse birth outcomes. Methods: A one-time survey of 119 mothers in the program and monthly semi-structured interviews with 41 mothers, totaling 220 interviews. Results: Almost all mothers reported significantly reduced stress after joining the program. The majority also reported an improved sense of safety, security, and hope. Interviews show additional moderate reductions in stress over time while being a program client. Interviews also indicate that mothers’ relationship with their CHW is key to these improvements: CHW provide social-emotional support, access to tangible goods, and help navigating social service bureaucracies. Discussion: The results support the broader literature on the health benefits of community health workers and address identified gaps within the literature, which has infrequently studied CHWs in the perinatal context. Conclusion: CHWs may be one way to address racial inequity in birth outcomes linked to infant mortality, given research on the links between inequitable exposure to stressors, the impacts of racism-induced stress, and preterm and low birth weight babies. Further, the findings indicate the need to better support CHWs, and the programs that utilize them, with increased funding, insurance reimbursement, and certification.